Clinical efficacy and safety of traditional Chinese medicine Xiao Yao San in insomnia combined with anxiety. Issue 43 (29th October 2021) - Hu, Jing; Teng, Jing; Wang, Wanyu; Yang, Ni; Tian, Haoyu; Zhang, Wei; Peng, Xiangyu; Zhang, Jingyu
Abstract: Background: Patients with long-term insomnia generally experience anxiety and depression. Traditional sleeping pills and anti-anxiety drugs have certain limitations. Xiao Yao San (XYS), a complementary and alternative therapy, has been widely used to treat insomnia combined with anxiety. This study aims to evaluate the efficacy and safety of XYS in the treatment of insomnia combined with anxiety. Methods: Related literature was retrieved from 8 electronic databases from the establishment time to March 2021. The subjects were diagnosed with insomnia combined with anxiety. We assessed the methodological quality of randomized controlled trials (RCTs) according to the Cochrane Handbook. Data analysis was conducted using RevMan 5.3 software. Results: The analysis includes 9 RCTs involving 681 patients. Meta-analysis supported that as an auxiliary drug for Western medicine (WM), XYS could enhance the clinical efficacy of insomnia calculated according to the traditional Chinese medicine (TCM) syndrome score scale (risk ratio [RR]: 1.26; 95% confidence interval [CI]: 1.13–1.43; P = .0002) and reduced the scores of Hamilton Anxiety Scale (mean difference [MD]: −5.19; 95% CI: −7.78 to −2.60; P < .001), Pittsburgh Sleep Quality Index (MD: −3.35; 95% CI: −4.86 to −1.84; P < .001), Self-rating Anxiety Scale (MD: −9.38; 95% CI: −10.20 to −8.75; P < .001), TCM syndrome score scale for insomnia (MD: −4.45; 95% CI: −6.65 to −2.24; P < .001), and TCM syndrome score scale for anxiety (MD: −5.54; 95% CI: −9.48 to −1.6; P = .006). The summary analysis also shows that the separate use of XYS was advantageous in reducing the scores of the Hamilton Anxiety Scale (MD: −3.70; 95% CI: −6.31 to −1.09; P = .005), Pittsburgh Sleep Quality Index (MD: −1.82; 95% CI: −2.39 to −1.24; P < .001), and Self-rating Anxiety Scale (MD: −10.79; 95% CI: −14.09 to −7.49; P < .001). The incidence of adverse events with XYS as an ancillary drug or used separately was lower than that in the WM. Conclusion: Our systematic evaluation and meta-analysis showed that XYS combined with WM or XYS alone was beneficial for improving sleep quality and relieving anxiety. Due to the low methodological quality, small sample size, and significant heterogeneity of RCTs, more rigorous and scientific clinical trials are required to further evaluate the efficacy and safety of XYS. PROSPERO registration number: CRD42020190613.